Direct versus indirect strategies for thyroid hormone reference intervals established in a middle-aged and elderly population on an immunoassay analyzer. Issue 3 (2010) - Motor, Sedat; Erden, Gönül; Sahillioğlu, Birsen; Erdoğan, Serpil; Yıldırımkaya, Mustafa Metin
No abstract available